Strategi Komunikasi Indonesia Memperkuat Posisi sebagai Pusat Gaya Busana Muslim Global - Yusuf, Ramayani; Haerani , Hanni; Yulianita, Neni (CV. ITTC INDONESIA, 2025)
Indonesia has long been known as one of the centers of the global Muslim fashion industry. This research analyzes communication strategies that Indonesia can implement to strengthen its position in the international Muslim fashion scene. Using a qualitative approach, the research was conducted through literature studies, in-depth interviews with stakeholders in the Muslim fashion industry , and analysis of creative industry development policies. The research results identify five main communication strategies: (1) developing the narrative